Effect of Genetic-Environmental Interaction on Chinese Childhood Myopia - Xiyan Zhang; Yan Wang; Chenwei Pan; Wenyi Yang; Yao Xiang; Jie Yang; Fengyun Zhang (Journal of Ophthalmology)
Objective. The purpose of this study was to evaluate the effect of genetic-environmental interaction on myopia in Chinese children aged 6 to 9 years. Methods. Students had the physical examination and were required to provide basic demographic information. Their families were asked to fill in a questionnaire concerning factors related to myopia. Multiple regression analysis was performed, and adjusted risk ratio values were calculated to assess the role between gene and environment. Value of the environmental and genetic index (EGI) was calculated to demonstrate the effect of genetic-environmental interaction on myopia. Results. The prevalence of myopia maintained at a high level. EGI was calculated as 0.125 suggesting that genetic factors may play the 12.5% role in the formation of myopia and environmental factors may play a role of 87.5% in the formation of myopia. Conclusions. For young pupils aged 6 to 9 years, myopia prevalence maintained at a high level, and duration of homework time and staring at electronic screen were the strongest factors associated with myopia. The calculated value of EGI was low, which suggests that environmental factors may play the leading role in the formation of myopia. A long-term follow-up research to improve the accuracy value of EGI is our next job.